Synopsis of Results on the Impact of Community-Based Health Insurance on Financial Accessibility to Health Care in Rwanda - Schneider, Pia; Diop, François (World Bank, Washington, DC, 2013)
This paper evaluates the impact of prepayment schemes on access to health care for poor households, based on household survey data. Rwanda is one of the poorest countries in the world. After the genocide in 1994, public health care services were provided for free to patients, financed by donors and the government. In 1996, the Ministry of Health reintroduced prewar level user charges. By 1999, utilization of primary health care services had dropped from 0.3 in 1997 to a national average of 0.2 annual consultations per capita. This sharp drop in health service use combined with growing concerns about rising poverty, poor health outcome indicators, and a worrisome HIV prevalence among all population groups motivated the Rwandan government to develop community-based health insurance to assure access to the modern health system for the poor. The findings presented in this paper reveal that insurance enrollment is determined by household characteristics such as the health district of household residence, education level of household head, family size, distance to the health facility, and radio ownership, whereas health and economic indicators did not influence enrollment. Insurance members report up to five times higher health service use than nonmembers.